STRATEGIES TO MOTIVATE STUDENTS IN THE LEARNING PROCESS OF ENGLISH IN THE 8TH GRADE OF BASIC EDUCATION PARALLEL “A” IN TÉCNICO LICTO HIGH SCHOOL DURING THE SCHOOL YEAR 2014-2015 - CALLE RUILOVA, MAYRA VIVIANNA (2016)
At the time of observing the institutional development one of the major problems was the use of few strategies to motivate which prevents the efficient performance of the Técnico Licto high school. Since, strategies and techniques are very necessary learning resources for teaching nowadays. Besides, strategies and techniques are designed to lead to better learning, because of them; we can develop the knowledge, acquire skills with less effort and incorporate the ideals and attitudes that we as future teachers must provide our students. The following research aims to prove whether the use of motivational strategies influence positively in the learning process of English. To address the issue at hand, we will start by explaining that a key factor at the time of learning the language is motivation which has to do no more than the strategies used by the teacher. This itself has become a main objective to decrease difficulties when teaching.